SMALL BOWEL CONTUSION AND PERFORATION DUE TO UNCOMMON BLUNT ABDOMINAL TRAUMA - Nikšić, Hana; Vasin, Dragan; Tadić, Boris; Raspopović, Miloš; Perišić, Zlatko; Božić, Mirjana; Hasanagić, Sanela; Mašulović, Dragan (Sanamed, 2023)
Introduction: Small bowel injuries are rare, accounting for only 1% - 5% of injuries following blunt abdominal trauma, while small bowel perforation has been reported in 0.3% of patients. Delays in early diagnosis or misdiagnosis significantly contribute to the mortality and morbidity associated with small bowel injuries. Blunt abdominal trauma poses a diagnostic challenge, with focused assessment using sonography in trauma and computed tomography abdomen becoming invaluable methods for diagnosis, integrated into management guidelines.Case Report: We present a case of jejunal perforation and contusion resulting from blunt abdominal injury due to a fall onto a fence. The initial chest X-ray did not reveal any traumatic injuries or subdiaphragmatic free gas. Computed tomography of the abdomen and small pelvis revealed free fluid in the peritoneal cavity and thickening of the jejunal wall, corroborated by abdominal ultrasound. Surgical intervention confirmed a diagnosis of small jejunal perforation.Conclusion: Given the minimal and often clinically undetectable signs in patients with blunt abdominal trauma, timely and accurate imaging diagnostics and prompt surgical intervention significantly reduce the morbidity and mortality associated with these injuries.
Keywords: Blunt abdominal trauma; Jejunal perforation; Contusion; Computed tomography; Surgery